Futsal Playing Skills in Futsal Extracurricular at SMK Pembangunan Pacitan - Alfindana, Dicky; Syafi'i, Mohammad; Nurcahyo, Rizky Wahyu; Muhakim , Syahrul (Fair Play, 2024)
The problem in the research carried out by group 12 educational intern students at Pacitan Development Vocational School was to identify the level of basic futsal playing skills of futsal extracurricular participants at Pacitan Development Vocational School. The aim of this research is to find out the level of basic futsal playing skills of students who take part in extracurricular futsal. The method used is a survey using sports measurement methods. Sampling used total sampling. The samples studied were 15 students at Pacitan Development Vocational School who participated in futsal extracurriculars with the samples taken namely shooting techniques and dribbling techniques. Data analysis was carried out using descriptive analysis, namely taking real data in the field and processing the data using Microsoft Excel. For the results of basic shooting techniques, the minimum value is 19, the maximum value is 24, the average is 21, and the standard deviation is 1.554858. Meanwhile, dribbling technique has a minimum value of 17.35, a maximum value of 14.57, a mean of 15.93, and a standard deviation of 0.940528.